LEAF MODIFICATIONS TO QUANTIFY YIELD, EARLINESS AND FIBRE TRAITS IN GOSSYPIUM HIRSUTUM L. (Biological Sciences - PJSIR, 2004)
4 2 Ten BC  : F  back-cross derived near-isolines developed from ten different cross combinations, differing in only leafshape i.e. Normal, Okra, Sub-okra and Super-okra were compared for quantifying their yield, earliness and fibre traits. Sub-okra leaf cotton (Lu2) was observed as an appropriate replacement for the normal leaf to improve the traits. Sub-okra types in all the combinations were superior for most of the traits. On an average over the populations, Sub-okra gave 19.7% higher yield, 1.5% earliness, 4.7% longer fibre and 2.1% more uniform fibre than the normal leaf isolines. Nevertheless, Sub-okra ginned and gave equally better fibre strength with the normal leaf. Yield, earliness, longer and uniform fibre superiority of Sub-okra leaf cotton over the normal leaf coupled with established insect resistance of modified leaves suggested that the potentiality of mutant leaves be exploited in future breeding programmes.